Data acquisition for image sensor based tomography - Sahlabadi, Sayed Amirhossein (2010)
Process tomography is a technique to realize flow imaging in a process vessel or pipeline by using the sensor system. It can be applied to many types of processes and unit operation, including stirred reactors, pipelines, mixers, fluidized bed and separator. Process tomography is a vital area of research involving image reconstruction and velocity measurement. The target of this project is to develop a tomography system by using CMOS linear base optical sensors with four light sources for revelation of solid flow. Several researches had been carried out in the same field but with the use of CCDs and optical fibers, where else in this project CMOS sensor with a resolution of 1024 pixels, which produces a high resolution image of investigating area, is used. The precision of the image obtained is dependent on the number of sensors used and the projection technique applied. In this project parallel beam projection technique has been used with four light sources as the transmitters and four CMOS sensors as the receivers. The analog signals received by the sensor are computed and send to the data acquisition system for analog to digital conversion. Using the microcontroller these data will be sent to the computer for processing and image reconstruction.